Proceso atención de enfermería en paciente adulta de 38 años de edad con diabetes mellitus no insulino dependiente más amputación total de miembro inferior izquierdo. - Pimentel Segura, Gabriela Alejandra (2023)
Diabetes mellitus 2 appears when the body does not respond adequately to insulin, necessary to mobilize blood sugar. This action is called insulin resistance, meaning fat, liver, and cells do not respond to this hormone. Therefore, blood sugar does not enter them to be stored as energy. Diabetic neuropathy, in fact, is the first ulcer onset factor. Diabetic foot ulcers usually become easily infected, this coupled with circulation problems and damage to nerves and blood vessels, draws less blood to the tissues, which can lead to gangrene. This can lead to the need for amputation. The present clinical study addresses the case of a 38-year-old patient, suffering from Diabetes Mellitus II who presents ulcerated areas at the level of the lateral aspect of the leg and on the anterior aspect of the ankle, blisters can be seen in a state of necrosis on the leg. . The benefits that this clinical study will bring reside in the promotion of knowledge about the occurrence in a patient and the care process that has been applied, to prevent complications caused by poor compliance with treatment and ineffective care of their lifestyles and with it Avoid economic costs to the family.